Comparison of the short-term results of nasal and temporal 180° selective laser trabeculoplasties for open-angle glaucoma - Paula,Jayter Silva (2022)
ABSTRACT Purpose: The nasal sector of the anterior chamber angle may present a higher density of collector channels, which may influence the results of angle surgeries. Considering the anatomical differences in the anterior chamber angle, we compared the results of the nasal and temporal 180° selective laser trabeculoplasty approaches for open-angle glaucoma. Methods: A retrospective chart review was conducted for patients with open-angle glaucoma (primary, pseudoexfoliation, and pigmentary) who underwent at least one 180° selective laser trabeculoplasty session between December 2016 and October 2018. The nasal (N1) or temporal (T1) sectors were chosen at the physician’s discretion. Patients who did not experience decreased intraocular pressure between 3 and 6 months again underwent 180° selective laser trabeculoplasty in the opposite angle sector (T2 and N2). The main outcome measured was decrease in intraocular pressure at 6-month follow-up, after the last selective laser trabeculoplasty. A multivariable regression analysis was used to evaluate factors associated with decreased intraocular pressure after treatment. Results: The procedure was performed initially in 45 eyes (N1, 25; T1, 20 eyes) and repeated in the opposite anterior chamber angle sector in 19 eyes (N2, 11; T2, 8 eyes). Analysis of variance revealed that only the N1 approach presented a significant difference in the decrease in intraocular pressure as compared with the T1, N2, and T2 approaches (p=0.0014). The baseline intraocular pressure (p=0.021) and anterior chamber angle sector (N1; p=0.044) correlated with decreased intraocular pressure. Conclusion: Compared with the temporal approach, 180° selective laser trabeculoplasty performed initially in the nasal sector was associated with a more significant decrease in intraocular pressure. Considering the sectorial differences in the anterior chamber angle, further prospective trials are warranted to confirm our findings and provide more-efficient selective laser trabeculoplasty protocols.